(untitled) (Journal of Advanced Research in Journalism & Mass Communication, 2018)
In recent years Digital Resource has become increasingly important towards educational system to be changed in the near future. Information and Communication Technology (ICT) is the new technologies that deliver on high-tech e-learning services in our world including India. The Educational e-Resources are e-Journals, e-books and multimedia productions, etc. Indian government has initiatives on Digital Media e-Resources, are less expensive and more useful for academic development. Moreover, Indian initiative open access “Shodhganga” is Facilitates e-resource portal for Indian theses and dissertations to the world academic community. The rise of Web media 2.0 suggests many reasons for introducing new technologies in education (Bates, 2000) like, for example, improving the quality of E-education, reducing the costs and getting new revenues, accessing to new educational markets, and supporting the process of modernisation of the universities. Also, a rather large body of literature (especially from the USA) emphasizes the dramatic changes in the higher education system caused by the diffusion of new educational technologies, as well as the need for universities to radically change in order to stand both the social pressure and the competition from online universities (Bates et al., 2000). Moreover, Indian Governement frequently invest money and adequate efforts to digitize higher education through subsequently providing E- resources through digital media, e-portals are apparently familiar amongst them. This paper tries to highlight the importance of e-Resource use and how they are access for academic performance and knowledge development. The data would be collected from University Students, Scholars and Teachers. Quantitative survey is applied in this study. How to cite this article: Ramaraj M, Radha B. A Study on Digital Media (E-Resource) Impact on the University Students in Tirunelveli. J Adv Res Jour Mass Comm 2018; 5(4): 26-29. DOI: https://doi.org/10.24321/2395.3810.201815